The pyramids - Weeks, John S. (Minneapolis : Lerner Publications Co., 1977)
Describes the construction and uses of Egyptian pyramids.
Includes index.
Keywords: Pyramids -- Egypt -- Juvenile literature; Pyramids; Egypt -- Civilization -- To 332 B.C.